Anticoagulant therapy innovations in ensuring for effectiveness and safety - V. Tindalsky (Лечащий Врач)
The Russian National Congress of Cardiology 2020 was held from September 29 to October 1. Due to the unfavorable epidemiological issues congress switched into online – 149 meetings in 15 virtual rooms. All the meetings were recorded and uploaded to the YouTube channel of the Russian Cardiological Society. There was a decent discussion about cardiology and multidisciplinary interaction. Special attention was payed to recently updated ESC Guidelines on Atrial Fibrillation 2020. Over the past 10 years, anticoagulant therapy has gone through a series of major events. The new guidelines have been generally well approved by both medical community and patients. Comprehensive assessment of risk factors in patients with atrial fibrillation is a key for the prescription of adequate treatment considering effectiveness and safety. The new era of direct oral anticoagulants was represented at satellite symposia by opinion leaders in cardiology.